Fragments in the archive the Khmer Rouge years - Hamilton, Annette (2018)
Access online through this link: https://www.plarideljournal.org/article/fragments-in-the-archive-the-khmer-rouge-years
Keywords: Cambodia. Khmer Rouge Tribunal; Motion pictures -- Cambodia; Film criticism